2015
DOI: 10.1186/s40643-015-0074-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a new thermostable and alkali-tolerant α-carbonic anhydrase from Lactobacillus delbrueckii as a biocatalyst for CO2 biomineralization

Abstract: Background: Carbonic anhydrase (CA, EC 4.2.1.1), an ancient enzyme and the fastest among many enzymes, is a useful biocatalyst for carbon capture use and storage (CCUS). The use of alkaline buffers and high temperatures are favorable for biomineralization. Hence, the stability of CA under such harsh conditions is extremely important for its practical application. Methods and results:Herein, we report a new thermostable and alkaline-tolerant α-CA (designated as LdCA), with only 26 % identity to bovine CA (BCA),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…An alkaline pH of 12 causes an activity decrease of approximately 20%, which is similar to that observed in our previous work in the absence of any nitrate [43]. The result is also consistent with Li et al [52], who observe a 50% loss in activity for a bacterial CA once the pH exceeds 6 irrespective of the ionic environment, with this activity stable from pH 8 to 11.0. The relatively small fall in activity also suggests that the LbL coating is still stable under these conditions, as the enzyme is not washed away during the three minute wash of the membrane with water prior to analysis.…”
Section: Effect Of Anions and Toxic Gases On The Activity Of The Immosupporting
confidence: 92%
See 1 more Smart Citation
“…An alkaline pH of 12 causes an activity decrease of approximately 20%, which is similar to that observed in our previous work in the absence of any nitrate [43]. The result is also consistent with Li et al [52], who observe a 50% loss in activity for a bacterial CA once the pH exceeds 6 irrespective of the ionic environment, with this activity stable from pH 8 to 11.0. The relatively small fall in activity also suggests that the LbL coating is still stable under these conditions, as the enzyme is not washed away during the three minute wash of the membrane with water prior to analysis.…”
Section: Effect Of Anions and Toxic Gases On The Activity Of The Immosupporting
confidence: 92%
“…Secondly, it indicates that the enzyme is significantly more thermostable. In prior work, carbonic anhydrase variants isolated from Lactobacillus delbrueckii[52] and the Gossypium hirsutum cotton plant[60] exhibited deactivation energy values of 185 kJ mol -1 and 146 kJ mol -1 , respectively, based on the Wilbur-Anderson activity assay method[61] for CO 2 hydration. Kanbar and Ozdemir[53] obtained values of 120 kJ mol -1 for free BCA and 360 kJ mol -1 for BCA immobilized within a polyurethane foam.…”
mentioning
confidence: 99%
“…As list in Table , the k cat and k cat / K m for several different types of CA from Bovine b CA, human h CAI and h CAII, Helicobacter pylori ( Hp CA) and wild type S. yellowstonense ( Ssy CA) are lower than that of Sy CA. Besides, Sy CA has 22,892 WAU/mg is much higher than Ld CA from Lactobacillus delbrueckii (i.e., 454 WAU/mg) . Herein, the heterologous expression of Sy CA by E. coli is after optimization and with higher productivity.…”
Section: Resultsmentioning
confidence: 93%
“…Besides, SyCA has 22,892 WAU/mg is much higher than LdCA from Lactobacillus delbrueckii (i.e., 454 WAU/mg). 34 Herein, the heterologous expression of SyCA by E. coli is after optimization and with higher productivity.…”
Section: Characterization Of Sycamentioning
confidence: 99%
“…A similar study was also reported in bacteria from Firmicute phylum. Alkali stable (9.0) and thermostable (50°C) a-CA reported from Lactobacillus delbrueckii is favourable for carbonation and biocalcification (Li et al 2015). The economic feasibility is also essential for the commercialization of technology.…”
Section: Development In Ca-based Mineralization and Phylogenetic Distmentioning
confidence: 99%